1995
DOI: 10.1143/jjap.34.1153
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Growth of GaN on Various Substrates by Gas Source Molecular Beam Epitaxy Using RF-Radical Nitrogen Source

Abstract: Two dimensional (2D) layer by layer growth conditions for GaN epita,xial layers by gas source molecular beam epitaxy using a 13.56 MHz RF-radical nitrogen source were systematically investigated for the first time. It was clarified that the lower growth rate @<0.1 pm/h) enhanced the 2D growth. Furthermore, the introduction of annealed thin Gal.I buffer layer (60 A) drastically enhanced the 2D growth for the layers grown,on (0001) Al2O3, (001) MgO and (001) GaAs substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For growth of c-GaN on GaAs͑001͒, 1 ϫ 1, 2 ϫ 2, and c͑2 ϫ 2͒ reconstructions were reported. [4][5][6][7] A ͱ 10ϫ ͱ 10− R 18.4°reconstruction was also reported. 1,2 The growth of c-GaN͑001͒ on SiC / Si͑001͒, by contrast, resulted in 1 ϫ 1 and 4 ϫ 1 reconstructions which are correlated with the sample temperature and the Ga flux during growth.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…For growth of c-GaN on GaAs͑001͒, 1 ϫ 1, 2 ϫ 2, and c͑2 ϫ 2͒ reconstructions were reported. [4][5][6][7] A ͱ 10ϫ ͱ 10− R 18.4°reconstruction was also reported. 1,2 The growth of c-GaN͑001͒ on SiC / Si͑001͒, by contrast, resulted in 1 ϫ 1 and 4 ϫ 1 reconstructions which are correlated with the sample temperature and the Ga flux during growth.…”
Section: Introductionmentioning
confidence: 81%
“…The topic of cubic GaN has attracted and received much attention due to the direct wide band gap and tetrahedral zinc-blende bonding structure, which could lead to the growth of GaN alloys and heterostructures with other tetrahedral zinc-blende structure semiconductors. [1][2][3][4][5][6][7][8][9][10][11][12] A number of different atomic reconstructions have been observed on c-GaN͑001͒, depending on the growth conditions and the substrate. For growth of c-GaN on GaAs͑001͒, 1 ϫ 1, 2 ϫ 2, and c͑2 ϫ 2͒ reconstructions were reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, under N-rich growth conditions, a wurtzite GaN layer grew preferentially. On the other hand, Kikuchi et al [7] described the growth of GaN on MgO(0 0 1), and they reported a 1 Â1 reconstruction during the growth.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major difficulties lies in the deficiency of an ideal substrate that matches well to GaN from both lattice and thermal expansion points of view. Because the high interfacial energy between GaN layer and sapphire substrate leads to a threedimensional (3D) island growth, the GaN, InN, or AlN nucleation layer growth and annealing are necessary processes [4][5][6]. In order to improve the quality of GaN epitaxial layer, the influences of growth parameters such as nucleation layer [7], thermal annealing [8], growth temperature [9], V/III ratio [10], pressure [11], thickness [12], etc., have been well studied.…”
Section: Introductionmentioning
confidence: 99%